The Tafsir Al Qur’an dan Hadist tentang Konsep Produksi dalam Perspektif Ekonomi Islam - Amelia, Dea; Alfiah, Rahma Sofia; Nur Shafiyah, Karina; Diyaanah, Faadhilatul; Ayu Ariany, Candra; Saidah, Nihayatus; Kurniawan, Taufiq (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Production is a fundamental component of economic activity that plays a strategic role in achieving human well-being. From an Islamic economic perspective, production is understood not only as a technical process aimed at creating or increasing the utility value of goods and services, but also as a manifestation of human responsibility as leaders on this earth. Using an Islamic economic interpretation of the verses of the Qur'an and hadith, this study aims to examine the concept of production in depth from an Islamic economic perspective. Using a descriptive-analytical approach, this research technique utilizes a literature review to examine Islamic economic literature and relevant interpretations, in addition to primary sources such as the Qur'an and hadith. The results show that the Qur'an and hadith provide a framework for production that integrates moral, social, and spiritual values ​​into economic activities, utilizes natural resources optimally and sustainably, and produces halal goods and services. Along with material gain, Islamic manufacturing aims to promote social justice, individual well-being, and ecological harmony. Therefore, the concept of production from an Islamic economic perspective makes economic activity a form of worship and a tool for developing well-being that adheres to the principles of Islamic law.